Citizen’s Perception on Eco-friendly Lifestyle for Conserving Endangered Oriental White Stork and Crested Ibis Bird Species in Japan – Case Studies in Toyoka, Sado and Konosu Cities (International Journal of Built Environment and Sustainability, 2023)
This study aims to find out the relationship between an eco-friendly lifestyle and the attitude towards conservation of endangered Oriental White Stork and Japanese Crested Ibis bird species in Toyooka, Sado, and Konosu cities in Japan. Citizens were surveyed to assess their willingness to spend an eco-friendly lifestyle to protect the above-mentioned endangered bird species through questionnaire surveys. Ecological Mind Evaluation Scale (EM Evaluation scale) developed by Tanaka and Joh (2012) based on Hirose model and Bandura’s research on Self Efficacy was applied in this research. This Ecological Mind Evaluation Scale includes 10 factors and it was applied to develop the questionnaire survey. The factor analysis was undertaken based on 4 groups of questionnaire results; environmental awareness, attitude towards environmental conservation, environmental consciousness and self-efficacy. Factor analysis was performed using the varimax method and sample data set comprised 686 valid responses from the three study sites. The KMO values were over 0.80 indicating the sampling was adequate. According to the factor analysis Sado city scored high for environmental awareness and environment consciousness. Toyooka city scored high on self-efficacy and environmental consciousness. Konosu city was compared with the Toyooka and Sado cities, where more advanced habitat conservation activities are already implemented. Findings displayed that the citizens in Konosu city had low awareness about these bird conservation activities, however, they are willing to contribute in such activities in the future. Thus, this study demonstrated that by engaging in environmentally friendly lifestyles, the citizens can contribute to habitat conservation of endangered bird species
Keywords: Oriental White Stork, Japanese Crested Ibis, habitat preservation, Ecological Mind Evaluation, factor analysis